Improving The Efficiency of State Management of Tour Guides in Da Nang - Duc Tho, Le (VNU Journal of Science: Policy and Management Studies, 2023)
The article uses the method of collecting secondary documents to study the status of state management of tour guides in Da Nang city in terms of policy promulgation, policy implementation, and inspection work. As a result, the article highlights some limitations in the current state management of tour guides in Da Nang. The article also suggests some solutions for improving the state management of tour guides in Da Nang today. Keywords: Tour guide; State management of tour guides; Da Nang tourism.